Regularities of complexation of indotricarbocyanine dyes with human blood serum proteins - Tarasau, Dmitri S.; Samtsov, Michael P.; Krasnoperov, Nikita N. (Journal of the Belarusian State University. Physics, 2022)
The interaction of indotricarbocyanine dyes with human blood serum proteins was studied. The spectral and fluorescent properties of dyes in butanol, Dulbecco’s sodium and potassium phosphate buffer (0.14 mol/L) with pH 7.4, and human blood serum solutions were determined. It was shown that the spectral properties of dyes in butanol differ significantly from the spectral properties in solutions of Dulbecco’s sodium and potassium phosphate buffer and human blood serum, and that butanol effectively extracts the molecules of the studied dyes that do not form covalently bound complexes with blood serum components. By analysing the extraction products, the proportion of covalent complexes of dyes with protein molecules was determined. It has been established that indotricarbocyanine dyes with a chlorine-substituted orthophenylene bridge in the conjugation chain are partially passes into butanol, the degree of extraction depends on the ratio of dye and protein concentrations. Thus, at a concentration of 10 mmol/L in 5 % human serum, the degree of extraction of these dyes is ~50 – 60 % respectively, the proportion of dye molecules in strong covalently bound complexes with blood serum components is ~ 40 –50 %. On the contrary, the dye with a free polymethine chain is extracted almost completely (91.4 % extraction rate). The indotricarbocyanine dyes are promising for use as a photosensitisers for photodynamic therapy.
Keywords: indotricarbocyanine dyes; complexation; fluorescence spectroscopy; blood serum proteins; extraction; photosensitisers; photodynamic therapy